WORK-RELATED INJURIES NOTIFIED IN THE WORKER HEALTH INFORMATION SYSTEM - Eloise Cristine Franz; Marcia Casaril dos Santos Cargnin (Universidade Federal do Paraná, 2018)
Objectives: Describe the sociodemographic and work-related characteristics and identify the work-related injuries, reported in the Worker Health Information System of the State of Rio Grande do Sul. Method: A descriptive documentary study that gathered information by examining the records of the Individual Disease Notification Report, year 2015, at the Sistema de Análise de Negócios (SAN) of the 26 municipalities comprised by the 19th Regional Health Department of Rio Grande do Sul. Data analysis used simple and relative frequency calculation. Result: In total, 1,016 injuries were reported, mostly in men: 760 (74.8%); aged 18-29 years: 273 (26.8%). The most commonly reported injury was other occupational accidents, 787 (77.5%); 809 (79.6%) occurred in the workplace and 398 (39.2%) in the urban area. Conclusion: Most injuries (accidents and illnesses) involved young individuals, at working age, often resulting in permanent physical and mental disabilities.